Metal-organic frameworks derived single atom catalysts for lithium sulfur batteries - Feiyang Liu; Chenxu Dong; Chunsheng Yan; Yunfeng Li; Xu Xu; Liqiang Mai (Communications Materials)
Abstract Lithium-Sulfur (Li-S) batteries, though promising for next-gen storage, are stymied by polysulfide shuttling and anode dendrite growth. Single atom catalysts (SACs), with their high atomic utilization and exceptional catalytic performance, offer a viable solution and are extensively employed in high-energy-storage systems. Among synthesis routes, metal-organic framework (MOF)-derived SACs uniquely combine ordered porosity with atomically dispersed metals to tackle both cathode and anode issues in Li-S batteries. This review comprehensively outlines the most recent developments of MOF-derived SACs for sulfur cathodes, lithium metal anodes, and separators, focusing on their mechanisms and roles in enhancing polysulfide redox kinetics and mitigating lithium dendrite growth. Additionally, the text explores the obstacles and outlines future research orientations for practical uses. Overall, recent research indicates that MOF-derived SACs can accelerate the industrialization of Li-S batteries and provide a blueprint for next-generation design.